THE EFFECT OF SMALL GROUP DISCUSSION METHOD ON STUDENT’S READING COMPREHENSION FOR THE STUDENT ELEVENTH GRADE SENIOR HIGH SCHOOL - Rudi Rudi; Sofian Sofian; Iwan Supardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research aims at seeing the effect of the Small Group Discussion Method on Student’s Reading Comprehension in the level of XI Senior High School. The form of this research is library research. This research was done by analyzing three research journals on the Small Group Discussion Method. The researcher uses three reserch relevant journals from Darise with pre-Experimental research design, Noorhaya Sari using pre- Experimental research design, and Nur Indah with Pre-Experimental design. All the data sources taken from online resource. After the researcher analzing the data, the researcher found that, from Nilma Darise, the data showed Ho was rejected and H1 was accepted because the t-ratio value was higher than the t-critical value (3.76> 2.00). Nur Indah t ratio value is also higher than the t- critical value (9.30>1.72). Noorhaya Sari). Then, t- ratio value is higher than t-critical value (10.270 > 2.032). Apart from different techniques and samples of the analysis, all the resources show that the Small Group Discussion is able in improving student’s reading comprehension. In the other words that Small GroupDiscussion Method on Student’sReading Comprehension affect significantly to the Student’s Eleventh Grade Senior Highschool.Keywords: Reading Comprehension, Small Group Discussion Method